Registered access: authorizing data access. (December 2018) - Dyke, Stephanie; Linden, Mikael; Lappalainen, Ilkka; Argila, Jordi; Carey, Knox; Lloyd, David; Spalding, J.; Cabili, Moran; Kerry, Giselle; Foreman, Julia; Cutts, Tim; Shabani, Mahsa; et al.
Abstract The Global Alliance for Genomics and Health (GA4GH) proposes a data access policy model—"registered access"—to increase and improve access to data requiring an agreement to basic terms and conditions, such as the use of DNA sequence and health data in research. A registered access policy would enable a range of categories of users to gain access, starting with researchers and clinical care professionals. It would also facilitate general use and reuse of data but within the bounds of consent restrictions and other ethical obligations. In piloting registered access with the Scientific Demonstration data sharing projects of GA4GH, we provide additional ethics, policy and technical guidance to facilitate the implementation of this access model in an international setting.